Effect and Management of Excess Weight in the Context of Fertility-Sparing Treatments in Patients With Atypical Endometrial Hyperplasia and Endometrial Cancer: Eight-Year Experience of 227 Cases - Shan, Ying; Qin, Meng; Yin, Jie; Cai, Yan; Li, Yan; Gu, Yu; Wang, Wei; Wang, Yong-xue; Chen, Jia-yu; Jin, Ying; Pan, Ling-ya (Frontiers in Oncology, 2021)
Objective To investigate the oncologic and reproductive outcomes of fertility-sparing treatments (FSTs) in atypical endometrial hyperplasia (AEH) and endometrial cancer (EC) patients with excess weight (EW). Methods This retrospective study comprised patients with AEH or EC who achieved a complete response (CR) after FST from 2010 to 2018. The clinical characteristics, oncological and reproductive outcomes were compared between the excess weight (EW) group (body mass index (BMI)≥25 kg/m2) and normal weight (NW) group (BMI<25 kg/m2). The risk factors associated with recurrence and unsuccessful pregnancy in patients with EW were analyzed. Results Overall, 227 patients were enrolled, including 139 (61.2%) in EW group and 88 (38.8%) in NW group. In patients with EW, the pregnancy rate, the live birth rate and the relapse rate were 29.8%, 23.4%, and 30.9%, respectively. In patients with NW, these rates were 61.1%, 47.2%, and 31.8%, respectively. No significant differences were observed in the time to remission (P=0.865) and disease-free survival (DFS) (P=0.750). Patients in NW group achieved a better pregnancy rate than patients in the EW group (P=0.034). The patients with EW using ovulation induction to increase fertility tended to have a shorter time to pregnancy (P=0.042). However, no significant risk factors associated with unsuccessful pregnancy were identified after the multivariate analysis. In terms of DFS, the combination of gonadotropin-releasing hormone agonist (GnRH-a) and LNG-IUD was better for patients with EW than GnRH-a or oral progestin therapy alone (P=0.044, adjusted hazard ratio (HR)=0.432, 95% confidence interval (CI): 0.152-1.229), especially for patients with EW diagnosed with EC (P=0.032). Conclusion FSTs for overweight and obese patients should be more individualized. GnRH-a and/or LNG-IUD may be options prior to FSTs in patients with EW. Further prospective studies are needed.